The effect of medial arch support over the plantar pressure and triceps surae muscle strength after prolonged standing (Faculty of Medicine Universitas Indonesia, 2015)
Background: The activity with prolonged standing position is one of the causes of abnormalities in the lower leg and foot. The aim of this study is to discover the effect of medial arch support over the distribution of plantar pressure when standing and walking. Methods: This was an experimental study with pre- and post-design the strength of triceps surae muscle after prolonged standing, was also evaluated in an experimental study with pre- and post-design. Variables of plantar pressure measurement are the contact area and pressure peak were measured by using the Mat-scan tool. The measurement of the triceps surae muscle strength was done with a hand-held dynamometer, before and after using the medial arch support. Measurement was performed before and after working with prolonged standing position which took place about seven hours using the medial arch support inserted in the shoes. Data was analyzed using paired T-test. Results: There was a significant difference of peak pressure between standing (p = 0.041) and walking (p = 0.001). Whereas the contact area showed a significant decrease in the width of the contact area when standing (104.12 ± 12.42 vs 99.08 ± 10.21 p = 0.023). Whereas, the triceps surae muscle strength pre- and post-standing prolonged did not indicate a significant difference. Conclusion: There was decrease in peak pressure when standing and walking and decrease in contact area when standing on plantar after used of the medial arch support after prolonged standing.